Along for the Ride: Intrahepatic Cholangiocarcinoma with Concomitant LECT2 Amyloidosis - Phoenix D. Bell; Aaron R. Huber; Tom C. DeRoche (Case Reports in Pathology)
We present a case of a 69-year-old Hispanic male with a past medical history of type II diabetes mellitus who presented with a two-month history of abdominal pain. A CT scan was performed which identified a liver mass. Biopsy of the liver mass revealed infiltration of normal liver parenchyma by atypical glands surrounded by pale eosinophilic material. The atypical glands were positive for CK7, while negative for CK20, CDX-2, and TTF-1, consistent with intrahepatic cholangiocarcinoma. A Congo red stain was performed, which highlighted salmon-orange areas, some with a globular appearance, around the glands and within the sinusoids and vasculature. Under polarized light, these areas displayed apple-green birefringence. These findings were consistent with amyloidosis, which was further supported by identification of ALECT2- (leukocyte chemotactic factor-2-) type amyloid on mass spectrometry. To our knowledge, this is the first documented case of intrahepatic cholangiocarcinoma arising in association with LECT2 amyloidosis.